Diagnostic Pitfalls of Discriminating Lymphoma-Associated Effusions. Issue 17 (May 2015) - Chen, Hung-Jen; Huang, Kuo-Yang; Tseng, Guan-Chin; Chen, Li-Hsiou; Bai, Li-Yuan; Liang, Shinn-Jye; Tu, Chih-Yen; Light, Richard W.; Salah-Eldin., Manal
<x xml:space="preserve">Abstract</x> Abstract High serum lactate dehydrogenase (LDH) level, immunologic defects, enlarged mediastinal lymph nodes, and frequent hydration and diuresis in lymphoma patients may affect the development of pleural effusion (PE). The study was to assess the clinical utility of "Light criteria" and the "recommended algorithm for investigating PEs" in patients with lymphoma. The characteristics of 126 PEs of lymphoma patients who underwent diagnostic thoracentesis between January 1, 2003, and April 30, 2012, were reviewed. Using Light criteria, 29 (23%) PEs were incorrectly classified. The sensitivity for exudates in Light criteria was 88% and the specificity was only 44%. In 32 transudates, PE LDH correlated with blood LDH concentration (P < 0.001, r = 0.66). Nine transudates were misclassified as exudates (50%; 9/18) just due to PE LDH more than two-thirds the upper limits. Among the 56 bilateral PEs, 33 (59%) were exudates. Ten (63%) polymorphonuclear (PMN)-predominant exudative PEs were malignant. Infective PEs were often mononuclear (67%) rather than PMN predominant. When a patient has lymphoma with either unilateral or bilateral PE, thoracentesis for microbiological testing and cytology is imperative. Carefully clinical correlation in addition to the result from Light criteria and differential cell count is essential for prompt management.